European Unification and the Dollar Problem: A Comment - Haberler, G. (Quarterly Journal of Economics, 1950)
Journal Article European Unification and the Dollar Problem: A Comment Get access G. Haberler G. Haberler Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 64, Issue 2, May 1950, Pages 306–310, https://doi.org/10.2307/1882697 Published: 01 May 1950